Weaning and Supplementation Increase Liveweight Gain of Bali (Bos javanicus) Cattle of Small-holder Farmers in Central Lombok, Indonesia - Dahlanuddin, Dahlanuddin; Yulianto, TB; Priyanti, A; Poppi, DP; Quigley, SP (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2012)
Abstract. One of the constraints for improving productivity of Bali cattle in west Nusa Tenggara Province is the low growth rate of weaned calves. Results of on-station experiments showed that Sesbania grandiflora (sesbania) supplementation can significantly increase live weight gain of weaned calves. The objective of this experiment was to investigate whether sesbania supplementation can increase live weight gain of weaned calves and improve farmer income. This experiment was carried out in Tandek, Labulia Village (treatment village) and in Kelebuh and Sukaraja villages (control villages) central Lombok District from April to October 2008. A total of 21 calves (9 males and 12 females) aged 237±7 days with initial live weight of 122.3±4.5 kg were monitored in Kelebuh and Sukaraja villages (control villages). During the same period, 25 calves (13 males and 12 females) aged 237±6 days with initial weight of 108.8±4.1 kg were monitored in Tandek Village (treatment village) and fed fresh sesbania at 1% dry matter of live weight. To ensure that sesbania was fed at the recommended level, regular weighing of sesbania offered by each farmer was conducted 2-3 times per week. All calves were weighed every month to determine live weight gain. Farmers from the control villages and other villages were invited to a field day conducted in the treatment village at the end of the experiment. The results showed that sesbania supplementation significantly increased live weight gain (0.36±0.01 kg/day for calves in the treatment village compared to 0.22±0.01 kg/day for those in the control villages), increased body condition and health of the calves and improved farmer income. Weaning management and supplementation with sesbania was very easy to implement so most of the farmers participated in this study stated that they were willing to continue this feeding management.Keywords: Bali calves, growth, early weaning, Sesbania grandiflora, LombokAbstrak. Salah satu permasalahan untuk meningkatkan produktivitas sapi Bali di NTB adalah rendahnya tingkat pertumbuhan pedet lepas sapih. Hasil kajian di pusat penelitian menunjukkan bahwa suplementasi dengan pakan lokal seperti daun turi terbukti dapat meningkatkan pertambahan bobot badan pedet lepas sapih secara nyata. Penelitian ini bertujuan untuk menguji apakah suplementasi dengan daun turi pada peternakan skala kecil dapat mempercepat pertumbuhan pedet lepas sapih dan meningkatkan pendapatan peternak. Penelitian dilakukan di Dusun Tandek, desa Labulia Lombok Tengah (lokasi intervensi) dan di Desa Kelebuh dan Sukaraja Kecamatan Praya Tengah (lokasi kontrol), Kabupaten Lombok Tengah mulai bulan April sampai Oktober 2008. Sejumlah 21 ekor pedet (9 jantan dan 12 betina) yang berumur 237±7 hari dengan bobot badan awal 122,3±4,5 kg diamati di Desa Kelebuh dan Sukaraja (lokasi kontrol). Pada saat yang sama, 25 ekor pedet (13 jantan dan 12 betina) berumur 237±6 hari dengan bobot badan awal 108,8±4,1 kg diamati di Tandek (lokasi intervensi) dan diberikan pakan tambahan berupa daun turi (sekitar 1% BK dari bobot badannya). Untuk memastikan jumlah daun turi diberikan sesuai dengan rekomendasi, dilakukan penimbangan daun turi yang diberikan secara acak dua sampai 3 kali seminggu. Penimbangan bobot badan dilakukan setiap bulan dan pada akhir penelitian dilakukan temu lapang dengan mengundang peternak dari lokasi kontrol dan lokasi lainnya di Lombok Tengah. Hasil penelitian menunjukkan bahwa penyapihan dan suplementasi daun turi secara nyata meningkatkan pertambahan bobot badan lepas sapih (0,36±0,01 kg/hari pada kelompok intervensi dibandingkan dengan 0,22±0,01 kg/hari pada lokasi kontrol), meningkatkan kondisi dan kesehatan pedet dan meningkatkan keuntungan peternak. Manajemen penyapihan dan suplementasi dengan daun turi sangat mudah dilakukan sehingga sebagian besar peternak yang berpartisipasi dalam temu lapang menyatakan bersedia menerapkannya.Kata kunci : Sapi Bali, pertumbuhan, penyapihan, Sesbania grandiflora, Lombok Dahlanuddin et al/Animal Production 14(3):173-179, September 2012